An analysis of the relationship between self-efficacy and learning approaches in university students - Pugnerova, Michaela; Kremenkova, Lucie; Plevova, Irena (e-Pedagogium, 2020)
Self-efficacy represents individual's beliefs about their capability to produce levels of activity that would achieve the desired goals or results. As task-specific self-confidence, self-efficacy is a key construct in various human activities and positions which is frequently mentioned in context of theory of motivation and learning. Learning approaches could be specified as a what person does when they are learning and why they should do it. Thus learning approaches are an important topic in the academic environment just as self-efficacy. The aim of this study is to analyse the relationship between self-efficacy and learning approaches. The research sample consisted of 710 university students (with mean age 22.61) of whom 116 were male and 594 were female. The data were obtained using the Revised Two Factor Study Process Questionnaire (R-SPQ-2F; Biggs, Kember, & Leung, 2001), measuring deep and surface approaches to studying, and the General Self-Efficacy Questionnaire (GSE, Schwarzer & Jerusalem, 1995) assessing optimistic self-beliefs to cope with a variety of difficult demands in life. The Pearsons correlation analysis confirmed the assumption suggesting a relationship between self-efficacy and learning approaches. Higher self-efficacy is positively correlated with deep approaches and negatively correlated with surface approaches. Subsequent partial correlations prove no effect of year and year of study on self-efficacy and learning approaches. Furthermore, inference tests did not show any significant differences in correlation coefficients (between self-efficacy and learning approaches) regarding gender and form of study. The implications and limitations of this study are discussed.
Keywords: university student; learning approaches; self-efficacy.